Pengaruh Financial literacy Terhadap Preferensi Masyarakat Kabupaten Tanah Datar Memilih Produk-Produk Pendanaan Pada Perbankan Syariah - Febby Irfayunita; Hesi Eka Puteri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
The purpose of this study investigates whether financial literacy affects the preferences of choosing the funding product at Islamic Banks. The research method used is a quantutative method that uses a sample of 385 customers of Islamic banks in Tanah Datar district, under condition 2018, this study reveals that financial literacy is positively associated with the preferences of choosing funding products. This finding offer the empirical evidence of the importance on the relationship of financial literacy to the preferences of choosing the funding product. It indicates that the financial literacy is a important point in Islamic banks thay will make peoples turn to Islamic banks . Furthermore, this research recommends strategy of increasing market share of Islamic Bank by increasing public’s finance literacy.